A peripheral CB2 cannabinoid receptor mechanism suppresses chemotherapy-induced peripheral neuropathy: evidence from a CB2 reporter mouse. Issue 5 (24th May 2022) - Lin, Xiaoyan; Xu, Zhili; Carey, Lawrence; Romero, Julian; Makriyannis, Alexandros; Hillard, Cecilia J.; Ruggiero, Elizabeth; Dockum, Marilyn; Houk, George; Mackie, Ken; Albrecht, Phillip J.; Rice, Frank L.; et al.
Abstract : Supplemental Digital Content is Available in the Text. Using a CB2 EGFP reporter mouse, we document peripheral cannabinoid mechanisms for suppressing chemotherapy-induced neuropathic nociception and elucidate CB2 -expressing cells that are dynamically regulated by paclitaxel. Abstract: CB2 cannabinoid receptors (CB2 ) are a promising therapeutic target that lacks unwanted side effects of CB1 activation. However, the cell types expressing CB2 that mediate these effects remain poorly understood. We used transgenic mice with CB2 promoter–driven expression of enhanced green fluorescent protein (EGFP) to study cell types that express CB2 and suppress neuropathic nociception in a mouse model of chemotherapy-induced peripheral neuropathy. Structurally distinct CB2 agonists (AM1710 and LY2828360) suppressed paclitaxel-induced mechanical and cold allodynia in CB2 EGFP reporter mice with established neuropathy. Antiallodynic effects of AM1710 were blocked by SR144528, a CB2 antagonist with limited CNS penetration. Intraplantar AM1710 administration suppressed paclitaxel-induced neuropathic nociception in CB2 EGFP but not CB2 knockout mice, consistent with a local site of antiallodynic action. mRNA expression levels of the anti-inflammatory cytokine interleukin-10 were elevated in the lumbar spinal cord after intraplantar AM1710 injection along with the proinflammatory cytokine tumor necrosis factor alpha and chemokine monocyte chemoattractant protein-1. CB2 EGFP, but not wildtype mice, exhibited anti-GFP immunoreactivity in the spleen. However, the anti-GFP signal was below the threshold for detection in the spinal cord and brain of either vehicle-treated or paclitaxel-treated CB2 EGFP mice. EGFP fluorescence was coexpressed with CB2 immunolabeling in stratified patterns among epidermal keratinocytes. EGFP fluorescence was also expressed in dendritic cells in the dermis, Langerhans cells in the epidermis, and Merkel cells. Quantification of the EGFP signal revealed that Langerhans cells were dynamically increased in the epidermis after paclitaxel treatment. Our studies implicate CB2 expressed in previously unrecognized populations of skin cells as a potential target for suppressing chemotherapy-induced neuropathic nociception.